APLIKASI PEMESANAN JASA LAYANAN FOTO MENGGUNAKAN ALGORITMA ROUND ROBIN - Aida Fitriyani; Hendarman Lubis; Andi Achmad (Fakultas Ilmu Komputer dan Desain - Unsurya, 2024)
The design of a web-based service booking system application is deemed necessary to make it easier for customers to order photography services and to assis in managing photographer schedules and to facilitate customer data management. In this thesis, the author uses the Round Robin algorithm to manage the use of resources in the service booking system. The Round Robin algorithm is a scheduling algorithm that is used to arrange assignments to several resources with the same amount sequentially and repeatedly. In the context of a service booking system application, this algorithm is used to manage advance payments and schedule the use of photographers for each service booking made by the user. Seeing the existing problems, we need a website-based booking system that provides all information about photography packages for weddings, pre-weddings and engagements offered. This research was conducted at from February to April 2023. This company is engaged in photography services for weddings, pre-wedding, and the engagement. the UML diagram designed, the database structure to be used, and displaying the system interface design to be built. Based on the results of the discussion and research on the design of the booking system regarding what has been done, the following conclusions can be drawn: This booking system makes it easier for customers to get information regarding the photography service packages offere. Keywords: Design, Booking System, Round Robin, Website